Assessment of the implementation of independent curriculum learning in Vocational High Schools - Jatmoko, Dwi; Basuki, Basuki; Nahdhatul Anhar, Fatah (Peneliti.net, 2023)
Assessment of the Implementation of the Independent Curriculum Learning Curriculum at Muhammadiyah Vocational School Purwodadi Purworejo. Automotive Engineering Education. FKIP. Purworejo Muhammadiyah University. 2023. The aim of this research was to determine the results of the independent curriculum learning assessment at Muhammadiyah Vocational School Purwodadi Purworejo. This type of research is Quantitative Descriptive research conducted on 31 teachers at Muhammadiyah Vocational School Purwodadi Purworejo. Data collection techniques use, questionnaires, and. The instrument used in this research was the Merdeka Curriculum learning implementation sheet. Data analysis in this research used quantitative descriptive. The results of the research show that the implementation of the independent curriculum learning was carried out well, this is in accordance with the results of the research descriptive data which in the very good category the percentage value was 39% and in the quite good category the percentage value was 35% with a difference in the number of respondents of 1 person so it is not close. It is possible that the process of implementing independent curriculum learning at Muhammadiyah Vocational School Purwodadi Purworejo still has many things that need to be improved so that the implementation of independent curriculum learning can be carried out very well, so that the implementation of the independent curriculum in schools in Purworejo district can be comprehensive, considering that currently only a few schools are implementing it. independent curriculum.